PENENTUAN TARIF SEWA KAMAR BERDASARKAN METODE ACTIVITY BASED COSTING PADA KOS MAHYA KECAMATAN KEDUNGWARU KABUPATEN TULUNGANGGUNG - Jamilatus Sholikhah; Dyah Pravitasari (ITB AAS Indonesia Surakarta, 2024)
The boarding house rental service business is a business that is not too big but the business is promising. Even though this business is not large, this business also requires cost control in order to produce accurate cost information. As is the case with Kos Mahya which is the research location. In determining room rental rates, the owner of the Mahya boarding house still follows market prices around the boarding house, which allows cost distortions to occur because they do not reflect specific activities. The need for an appropriate method for setting a room rate, namely the Activity Cased Costing method. The purpose of this study is to find out the determination of room rates using the Activity Based Costing method and a comparison of the activity based costing method with the method of the owner of the Mahya Boarding House regarding the determination of room rental rates. The research method used is descriptive quantitative. The results of the study show that the calculation of room rental rates using the Activity Based Costing method gives smaller results, compared to the determination of rates carried out by boarding owners based on market prices around the boarding house.